2014
DOI: 10.1002/bjs.9471
|View full text |Cite
|
Sign up to set email alerts
|

Performance of prognostic scores in predicting long-term outcome following resection of colorectal liver metastases

Abstract: Although available risk scores can predict DFS and DSS, none does so with sufficient discriminatory accuracy to identify all episodes of recurrent disease. A non-negligible proportion of patients develop recurrent disease beyond 5 years of follow-up and so surveillance beyond this point may be advantageous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 33 publications
(65 reference statements)
3
51
0
2
Order By: Relevance
“…(9) Roberts similarly showed in 286 patients with resected CRLM, that 6 of 7 CRSs identified cancer specific deaths at a frequency of less than 65% frequency. (12) Nomograms estimating outcomes after resection of CRLM are also poorly prognostic, achieving a maximum concordance index of only 0.61, and hence not identifying patients who will experience disease recurrence or death nearly 40% of the time (15, 31) Our findings concur with these studies – neither the Fong, Nordlinger, nor Iwatsuki CRSs were independently prognostic of OS in the validation cohort (Table 3). Notably, atleast 1 of the 3 CRSs failed to achieve significance on univariate analysis in both cohorts for both endpoints.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…(9) Roberts similarly showed in 286 patients with resected CRLM, that 6 of 7 CRSs identified cancer specific deaths at a frequency of less than 65% frequency. (12) Nomograms estimating outcomes after resection of CRLM are also poorly prognostic, achieving a maximum concordance index of only 0.61, and hence not identifying patients who will experience disease recurrence or death nearly 40% of the time (15, 31) Our findings concur with these studies – neither the Fong, Nordlinger, nor Iwatsuki CRSs were independently prognostic of OS in the validation cohort (Table 3). Notably, atleast 1 of the 3 CRSs failed to achieve significance on univariate analysis in both cohorts for both endpoints.…”
Section: Discussionsupporting
confidence: 79%
“…Patients were then divided into two groups: high risk (CRS >= 3) and low risk (CRS<3) based on established definitions. (13, 28, 29) Covariates with P<0.05 on univariate analysis were included in multivariate analysis, with a maximum of 7 degrees of freedom as per Harrell’s guidelines. (30) Survival probabilities were estimated using the Kaplan-Meier method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure describes the search results. The scientific literature review and web‐based search identified 53 tools predicting survival in colon or rectal cancer, reported across 63 articles . Two articles reported on the development of two tools each .…”
Section: Resultsmentioning
confidence: 99%
“…(Table 1) Importantly the beliefs of the speakers, most of whom are liver surgeons, may well have been aligned with this opening statement in another BJS paper: 'The surgical management of colorectal liver metastases (CRLMs) was a paradigm change in the management of metastatic disease and is one of the greatest advances in surgical practice of recent times.' [11] For liver surgeons, metastasectomy is the largest component of their work. Using this graph the speakers pointed out survival at five years as similar to that for patients who were stage III at the time of registration.…”
Section: Methodsmentioning
confidence: 99%